The association between lactate dehydrogenase to serum albumin ratio and the 28-day mortality in patients with sepsis-associated acute kidney injury in intensive care: a retrospective cohort study - Liang, Minghao; Ren, Xiuhong; Huang, Di; Ruan, Zhishen; Chen, Xianhai; Qiu, Zhanjun (Renal failure, 2023)
The mortality rate of patients with sepsis-associated acute kidney injury (SA-AKI) in the intensive care unit (ICU) is high, and there is a need for early identification of SA-AKI patients with poor prognoses. This study investigated the relationship between the lactate dehydrogenase to serum albumin ratio (LAR) and prognosis in patients with SA-AKI. We performed a retrospective cohort study of patients with SA-AKI who are represented in the Medical Information Mart for Intensive Care IV (MIMIC-IV). We used multivariable Cox regression analysis to determine adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). Subgroup analysis, survival curves, and curve fitting were used to evaluate a connection between the LAR and prognosis in patients with SA-AKI. There were a total of 6453 participants in this research. The average age of the participants was 63.9 ± 16.1 years, and the average LAR was 11.0 (7.6, 17.7)/IU/g. After controlling for variables, the HRs for 28-day mortality were 1.20 (HR: 1.20, 95% CI: 1.05-1.38, p = 0.008) and 1.61 (HR: 1.61, 95% CI: 1.41-1.84, p < 0.001) for Tertile 2 (T2, 8.59≤ LAR< 14.66) and Tertile 3 (T3, LAR ≥ 14.66), respectively, compared to Tertile 1 (T1, LAR < 8.59). The outcomes for 90-day mortality and in-hospital death rate were comparable. The Kaplan-Meier (KM) analysis revealed that the group with greater LAR had higher 28-day and 90-day death rates. Our study shows that LAR is associated with poor prognosis in patients with SA-AKI. Higher LAR is associated with higher 28-day, 90-day, and in-hospital mortality.